The legal regime of space objects - Шишка, Роман Богданович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The article is about the mode of space objects, first of all artificial. The author points out that if natural celestial bodies are opened for research and usage of all states without any discrimination, then for artificial ones the right of ownership is kept. Attention is drawn to the safety of humanity and non-admission of its extinction from encroachment on Earth of large space objects, to watching of orbits of space objects and readiness to change them in case of threats, arrangement of the use of space by space vehicles, its cleaning up from space garbage, usage of informative resources and minimization of consequences of economic scientific and other, in particular tourist, activity in space. It’s concluded in the article that recently with the development of technologies and resistance to prohibitions and restrictions as a component of space objects’ mode, grounded attempts to develop and clarify certain provisions of Outer Space Treaty, 1967 and the Agreement on the Activities of States on the Moon and other celestial bodies, 1979 were made. For instance, the agreement spreads on the Moon and other celestial bodies the mode of "Common heritage of mankind" and provides that the development of natural resources here should be an issue of a special international legal regime. However, nor the Agreement, neither other international treaties do not provide such a regime, that confirms an existence of a certain non-compliance. This proves that international space law regarding definition of celestial bodies’ mode stays in the area of desirable much more than in reality, and lots of actual issues remain beyond the reach of mankind. In the conclusion the author suggests that according to the legal regime of cosmic objects they are under special property rights – absolute rights.